LEGAL AND INSTITUTIONAL FOUNDATIONS FOR GUARANTEEING THE RIGHTS OF PERSONS WITH DISABILITIES AND THE PROVISION OF SOCIAL SERVICES - Kutpiddinov Xusniddin Muxiddinovich (Ecominds Press, 2026)
The article examines the normative-legal and institutional reforms implemented in the Republic of Uzbekistan during 2020–2025 aimed at improving the social protection system for persons with disabilities. The analysis emphasizes the significance of the Law “On the Rights of Persons with Disabilities” and its subsequent amendments, as well as constitutional guarantees of a social state designed to protect vulnerable segments of the population. The establishment of the National Agency for Social Protection and the “Inson” social service centers in 2023 is highlighted as a key step in enhancing the accessibility and quality of social services by bringing them closer to citizens. The article further discusses the digitalization of the disability assessment process, the introduction of the “IHMA enb” system, and the standardization of medical examinations, which reduced processing time and increased transparency. Strengthened monitoring and control mechanisms, including the activities of the Republican medical-social expert commission, are evaluated as important measures to reduce errors in disability determination. The modernization of rehabilitation and prosthetic-orthopedic services, the expansion of rehabilitation centers, the implementation of individual rehabilitation programs, and the voucher-based provision of technical aids are also analyzed. The conclusion indicates that reforms significantly enhanced the effectiveness of social protection, while emphasizing the need for continued development of monitoring, professional training for social workers, and public oversight.
Keywords: Persons with disabilities, social protection, normative-legal framework, rehabilitation, prosthetic-orthopedic provision, “Inson” center, digitalization, monitoring, legal guarantees, administrative liability.